Konsep Keadilan dan Kesetaraan Gender dalam Politik Indonesia: Perspektif Hukum Positif dan Hukum Islam - Indah Fitria Kumala Sari (At-Tafakur: Jurnal Ilmu Syari'ah dan Hukum, 2024)
This article aims to discuss the concepts of justice and gender equality in the Indonesian political context, by referring to the perspective of positive law and Islamic law. Gender justice is defined as fair treatment of women and men in various aspects of life, including in politics. This research identifies the challenges faced in achieving gender equality, such as discrimination and the absence of women's participation in political decision making. Through an analysis of the Al-'Adl principle and the principle of equality before the law, this article emphasizes the important role of the state in empowering women and eliminating gender inequality. This research uses a normative approach by conducting a literature study as a data collection method, then the data is processed and analyzed descriptively qualitatively. The research results show that awareness of justice and the elimination of gender discrimination is the key to creating conditions where women and men have equal rights and opportunities. It is hoped that this article can contribute to policy makers and society regarding gender equality and encourage joint efforts to achieve gender justice and equality in Indonesian politics.